Microalgae for CO₂ Capture Under Extreme Conditions and Its Biomass: A Mini Review - Fitria, Murni; Saputra, Anggi; Ahmad Farhan, Bahzad (Universitas Islam Indonesia, 2026)
The continuous increase in carbon dioxide (CO₂) emissions has raised atmospheric CO₂ concentrations to over 420 ppm. This has become one of the main drivers of global climate change, underscoring the need for efficient, sustainable mitigation strategies. Microalgae offer great potential for CO₂ capture. As photosynthetic organisms, microalgae use CO₂ for growth. They are reported to have photosynthetic efficiencies 10–50 times higher than those of terrestrial plants and to grow in various media, making them superior for carbon utilization. However, most conventional microalgae cannot thrive under extreme conditions, such as low pH (<4), high temperatures (>35 °C), high CO₂ levels (>10%), or the presence of pollutants like sulfur dioxide (SO₂) and nitrogen oxides (NOₓ). Extremophilic microalgae are species capable of surviving in highly acidic conditions, elevated temperatures, and environments contaminated with SO₂ and NOₓ. This makes them highly promising candidates for CO2capture under extreme conditions. Furthermore, microalgae capture CO2 and convert it into high-value biomass, thereby enhancing their value as CO2 capture agents.